Syntheses, Structures, Reactivities, and Basicities of Quinolinyl and Isoquinolinyl Complexes of an Electron Rich Chiral Rhenium Fragment and Their Electrophilic Addition Products - Molina, Dante A. Castillo; Wititsuwannakul, Taveechai; Hampel, Frank; Hall, Michael B.; Gladysz, John A. (Chemistry - A European Journal, 2021)
Reactions of Li+ [(η5-C5H5)Re(NO)(PPh3)]− with 2- and 4-chloroquinoline or 1-chloroisoquinoline give the corresponding σ quinolinyl and isoquinolinyl complexes 3, 6, and 8. With 3 and 8 there is further protonation to yield HCl adducts, but additions of KH give the free bases. Treatment of 3 with HBF4⋅OEt2 or H(OEt2)2+ BArf− gives the quinolinium salts [(η5-C5H5)Re(NO)(PPh3)(C(NH)C(CH)4C(CH)(CH))]+ X− (3-H+ X−; X−=BF4−/BArf−, 94–98 %). Addition of CF3SO3CH3 to 3, 6, or 8 affords the corresponding N-methyl quinolinium salts. In the case of [(η5-C5H5)Re(NO)(PPh3)(C(NCH3)C(CH)4C(CH)(CH))]+ CF3SO3− (3-CH3+ CF3SO3−), addition of CH3Li gives the dihydroquinolinium complex (SReRC,RReSC)-[(η5-C5H5)Re(NO)(PPh3)(C(NCH3)C(CH)4C(CHCH3)(CH2))]+ CF3SO3− ((SReRC,RReSC)-5+ CF3SO3−, 76 %) in diastereomerically pure form. Crystal structures of 3-H+ BArf−, 3-CH3+ CF3SO3−, (SReRC, RReSC)-5+ Cl−, and 6-CH3+ CF3SO3− show that the quinolinium ligands adopt Re⋅⋅⋅C conformations that maximize overlap of their acceptor orbitals with the rhenium fragment HOMO, minimize steric interactions with the bulky PPh3 ligand, and promote various π interactions. NMR experiments establish the Brønsted basicity order 3>8>6, with Ka(BH+) values >10 orders of magnitude greater than the parent heterocycles, although they remain less active nucleophilic catalysts in the reactions tested. DFT calculations provide additional insights regarding Re⋅⋅⋅C bonding and conformations, basicities, and the stereochemistry of CH3Li addition.
CRIS-Team Scopus Importer:2021-08-27
Keywords: basicities; crystal structures; DFT calculations; nitrogen heterocycles; rhenium; stereochemistry